2016
DOI: 10.1038/srep22964
|View full text |Cite
|
Sign up to set email alerts
|

Association between secondary thrombocytosis and viral respiratory tract infections in children

Abstract: Secondary thrombocytosis (ST) is frequently observed in children with a variety of clinical conditions. The leading cause of ST is respiratory tract infection (RTI) in children. Nasopharyngeal aspirate samples were collected and assessed for common respiratory viruses. The relationships between virus infections and secondary thrombocytosis were analyzed retrospectively. The blood platelet count and the presence of respiratory viruses were determined for 3156 RTI patients, and 817 (25.9%) cases with platelet ≥5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 29 publications
(30 reference statements)
9
41
0
3
Order By: Relevance
“…There is no current consensus in human or veterinary clinical pathology as to the most appropriate cutoff for classifying a thrombocytosis. Large retrospective studies and reviews of thrombocytosis in the human medical field have utilized a cutoff of >450–500 × 10 3 /μL to define a thrombocytosis, but a cutoff of >800 × 10 3 /μL to signify clinically relevant thrombocytosis . For the present study, the cutoff value of >500 × 10 3 /μL was extrapolated from past studies to establish disease correlation with higher platelet counts, as the clinical relevance of severity is unknown and investigating this was one of the objectives of the study.…”
Section: Discussionmentioning
confidence: 99%
“…There is no current consensus in human or veterinary clinical pathology as to the most appropriate cutoff for classifying a thrombocytosis. Large retrospective studies and reviews of thrombocytosis in the human medical field have utilized a cutoff of >450–500 × 10 3 /μL to define a thrombocytosis, but a cutoff of >800 × 10 3 /μL to signify clinically relevant thrombocytosis . For the present study, the cutoff value of >500 × 10 3 /μL was extrapolated from past studies to establish disease correlation with higher platelet counts, as the clinical relevance of severity is unknown and investigating this was one of the objectives of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmalarda çocuklarda sekonder trombositozların en sık nedeni olarak enfeksiyonlar bildirilmiş olup bizim çalışmamızda da aynı sonuca ulaşılmıştır. Solunum yolu enfeksiyonlarında trombositoza sık rastlanırken literatürde gastrointestinal ve üriner sistem enfeksiyonları da dikkat çekicidir [7].…”
Section: Gereç Ve Yöntemlerunclassified
“…The delta platelet count of 50 × 10 9 /L was determined as the cut-off value for the three groups to minimize the chance of misclassification of patients according to known normal variability of platelet counts measured by the counter (XE2000i, Sysmex, Japan) [15][16][17]. Thrombocytosis was defined as a platelet count > 500 × 10 9 /L, according to the relevant studies [9,11]. Fever was defined as an axillary temperature exceeding 38.0 °C.…”
Section: Study Definitionsmentioning
confidence: 99%
“…Previous studies on pediatric patients with bronchiolitis have focused on single platelet count determinations at hospital admission, and these studies found that the prevalence of thrombocytosis on admission ranged from 22.7% to 38.6% among consecutive patients with bronchiolitis [9][10][11]. The association between thrombocytosis on admission and disease severity in patients with bronchiolitis has been studied [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation